Strategy For Strengthening MSMEs Capabilities : Implementation Of Digital Marketing As A Means Of Promotion And Commercialization Of Business Products In The Kencana Village Of Bogor City - Nurhasanah, Meliani; Ameliasari, Sarah; Iskandar, Ade Irpan; Andria, Fredi (International Journal of Business, Economics, and Social Development, 2023)
Kencana Village has a lot of potential from the products produced by its people. Micro, Small and Medium Enterprises (MSMEs) in this area still market their products conventionally and have not marketed them through digital marketing. Even though digital marketing can really help MSMEs in the progress of their business. The large number of users of social media, e-commerce, Google and websites can be used as an opportunity for entrepreneurs to market the products they want. Activity objectives: increase the understanding and ability of the Kencana Village community regarding digitalization of MSMEs products, provide training regarding the use of digital media as a means of product promotion and commercialization, create an MSMEs website portal, and provide solutions related to problems experienced by local business actors in conducting sales and business promotions through digital media. The methods used are training and mentoring, media content creation practices, then data processing methods are also used through cobweb analysis and the Customer Satisfaction Index (CSI). The results of the spider analysis show that each competency parameter produces an average value of 4.76, indicating that all of them fall into the strongly agree category, as well as having a significant impact in increasing the knowledge and understanding of the participants. Meanwhile, research results regarding the level of satisfaction using the CSI method were found to be 89%, which shows that the public is satisfied with the training services provided. Results achieved: a) Increased understanding regarding digital marketing concepts and media that can be used to market MSME products, b) Increased skills related to creating product promotional content for social media and e-commerce, c) Creation of an MSME website which will be managed by the local MSME actors as a means of product promotion and commercialization, d) Motivation to implement digital marketing in Kencana Village, Bogor City.